2002
DOI: 10.1136/jnnp.72.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the management of optic neuritis: audit on the neurological and ophthalmological practice in the north west of England

Abstract: The management of acute optic neuritis by neurologists and ophthalmologists in the north west of England was assessed in the light of the Optic Neuritis Treatment Trial (ONTT) recommendations. A questionnaire on a fictitious case of typical unilateral optic neuritis was mailed to all consultant ophthalmologists and neurologists working in the North West and Merseyside Health Authorities. They were then asked to comment on management of the case. Fifty two out of 86 ophthalmologists and 20 out of 28 neurologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Any atypical presentations should prompt one to investigate further to exclude secondary causes of visual failure. 24,25,26 Indian's experience with optic neuritis is not very wide, but is consistent with the studies elsewhere. 27 In a long-term followup of recurrent ON, Pirko et al observed that 12.5% patients developed Neuromyelitis Optica (NMO) and another 14.4% developed MS.…”
Section: Discussionsupporting
confidence: 84%
“…Any atypical presentations should prompt one to investigate further to exclude secondary causes of visual failure. 24,25,26 Indian's experience with optic neuritis is not very wide, but is consistent with the studies elsewhere. 27 In a long-term followup of recurrent ON, Pirko et al observed that 12.5% patients developed Neuromyelitis Optica (NMO) and another 14.4% developed MS.…”
Section: Discussionsupporting
confidence: 84%
“…Not surprisingly, ophthalmologists and neurologists sometimes differ in their management of this condition (Ghosh et al, 2002). Since optic neuritis is a common early indicator for MS, neurologists more frequently recommend systemic steroids for the first presentation of optic neuritis (Chan, 2002), while ophthalmologists more frequently allow a single isolated episode of optic neuritis to recover naturally (Ghosh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It may be the first presentation of multiple sclerosis (MS) in almost 75% of female patients (Ghosh et al, 2002;Rizzo and Lessell, 1988) or represent onset of the highly aggressive optic nerve and spinal cord autoimmunity known as Devic's neuromyelitis optica (Wingerchuk et al, 1999). In all its manifestations, autoimmune optic neuritis is marked by both acute and chronic infiltration of immune cells into the optic nerve and their negative impact on myelinating oligodendrocytes (Lucchinetti et al, 2002;Ortiz-Ortiz et al, 1976).…”
Section: Introductionmentioning
confidence: 95%
“…However, the evaluation of the conversion of findings in clinical studies into actual practice -recently called "translational 2 research" -remains limited and difficult [2,32]. Surveys of practicing physicians can provide useful information regarding the translation of clinical trials into clinical practice [25,26]. However, surveys are often biased and low response rates limit their power [34].…”
Section: Discussionmentioning
confidence: 99%
“…Two surveys [25,26] performed a few years after the publication of the ONTT suggested that although the ONTT had apparently led to a substantial reduction in the use of oral prednisone alone in the treatment of acute optic neuritis, many physicians were not following evidence-based recommendations [25,26]. Such behavior raises the question of whether funded clinical trials in neurology and ophthalmology really translate into clinical practice [2].…”
Section: Introductionmentioning
confidence: 99%